Case report: systemic tuberculosis caused by Mycobacterium bovis in a cat - Eroksuz, Yesari; Baydar, Ersoy; Otlu, Baris; Dabak, Murat; Eroksuz, Hatice; Karabulut, Burak; Timurkan, Mehmet Ozkan (Bmc, 2019)
BackgroundThe diagnosis of previous cases of feline tuberculosis in Turkey has been made based solely on pathological changes without isolation of the causative agent. This case report details the first case of feline tuberculosis in Turkey for which the causative agent (Mycobacterium bovis) was confirmed with microbiological isolation, morphological evaluation, molecular (PCR) characterization and antibiotic sensitivity.Case presentationSystemic tuberculosis was diagnosed via postmortem examination of a 5-year-old stray male cat. Mycobacterium bovis was isolated from the lungs, bronchial and gastrointestinal lymph nodes, kidney and liver. The isolate was defined as M. bovis using the Genotype MTBC assay (Hain Lifescience, Germany), which allows differentiation of species within the Mycobacterium tuberculosis complex with an easy-to-perform reverse hybridization assay.Pathological changes were characterized by multifocal to coalescing granulomatous inflammation in the lungs, liver, lymph nodes and kidneys. Further pathological changes included severe, diffuse, hepatocytic atrophy, periportal fibrosis with lymphohistiocytic infiltration, multifocal lymphohistiocytic interstitial nephritis, mild focal pulmonary anthracosis and mild renal and hepatic amyloidosis. Infection by immunosuppressive viral pathogens including feline herpes virus-1, feline immunodeficiency virus and feline parvovirus virus were ruled out by polymerase chain reaction assay (PCR). The isolated mycobacteria were susceptible to isoniazid, ethambutol, rifampicin or streptomycin.ConclusionDisseminated M. bovis is a rare infection in cats. Involvement of submandibular lymph nodes suggested that primary transmission might have been the oral route in the present case.
Keywords: Feline tuberculosis; Pathological findings; Mycobacterium bovis; Systemic involvement